Increased systemic IL-6 levels indicate inflammation as a determinant component in renal cell carcinoma development - Cechim, Giovana; Ellwanger, Joel Henrique; de Lima Kaminski, Valéria; Berger, Milton; Bogo Chies, José Artur (Clinical and Biomedical Research, 2021)
Introduction: Renal cell carcinoma (RCC) is one of the most prevalent kidney tumors. It is believed that inflammation is a key factor for cancer progression and spread since inflammatory markers are generally associated with poor prognosis in RCC patients. Cytokines are cell communication molecules that act in both healthy and pathological situations. Of note, the processes of tumor growth and progression are mediated by cytokines. Recent findings suggest that cytokine level measurements could be used for cancer monitoring and prognosis. Methods: This study characterized and compared the systemic profile of different cytokines associated to the classical Th1, Th2 and Th17 immune responses in plasma samples from RCC patients (n=25) and healthy controls (n=29). Cytokine levels (IL-2, IL-4, IL-6, IL-10, TNF-α, IFN-γ, and IL-17A) were evaluated by flow cytometry using BD Cytometric Bead Array (CBA) kit. Results: No statistical difference in systemic IL-2, IL-4, IL-10, IL-17A, TNF, and INF-γ levels were observed between RCC patients and controls (p>0.05). On the other hand, higher systemic IL-6 levels were observed in RCC patients in comparison to controls (p=0.0034). Conclusions: This study highlights the importance of assessing the impact of IL-6 on RCC pathogenesis and its potential role as a biomarker of disease progression.